Biomechanical Analysis of Truncated Cone Implants for Maxillary Sinus Lift: An In Vitro Study on Polyurethane Laminas - Luca Comuzzi; Tea Romasco; Carlos Fernando Mourão; Giulia Marchioli; Adriano Piattelli; Natalia Di Pietro (Bioengineering)
This study aimed to evaluate the biomechanical performance of two truncated cone implant designs in maxillary sinus lift (MSL) procedures using polyurethane laminas. A total of 128 implants were used. Polyurethane laminas were divided into two groups based on thickness (1 and 3 mm) and two subgroups based on density (20 and 30 pounds per cubic foot, PCF). Each subgroup tested two implants (Sinus-plant and Sinus Lift Concept: SLC), resulting in 8 experimental conditions and 16 implants per condition. The insertion torque (IT), removal torque (RT), and implant stability quotient (ISQ) were measured. SLC implants achieved significantly higher IT and RT across all tested conditions (p < 0.0001), reporting the highest values at the 30 PCF/3 mm lamina (IT: 34.09 ± 0.32 Ncm; RT: 32.15 ± 0.29 Ncm) and the lowest at the 20 PCF/1 mm lamina (IT: 11.86 ± 0.22 Ncm; RT: 10.28 ± 0.22 Ncm). Additionally, SLC implants achieved significantly higher ISQ values, ranging from around 61 to 48 ISQ. Notably, this difference was not significant at the 20 PCF/3 mm lamina, highlighting that bone density may play a more critical role than thickness for SLC implants. This study simulated the clinical condition of achieving primary stability even with extreme maxillary bone thickness. The findings indicate that while both implant designs can be utilized in MSL procedures, the SLC is particularly effective in scenarios with limited bone thickness and density, potentially allowing for simultaneous MSL, implant placement, and healing screw application.